International business : competing in the global marketplace - Hill, Charles W. L. (Boston : McGraw-Hill/Irwin, 2009)
'International Business' addresses the strategic, structural and functional implications of international business in firms around the world.
Includes bibliographical references and index.
Keywords: International business enterprises -- Management; Competition, International